Odpowiedzi

Najlepsza Odpowiedź!
2010-03-22T22:23:25+01:00
A) -3x = 2x-10
-3x - 2x = -10
-5x = -10 / :(-5)
x = 2

c) 10 =4-2x
4-2x = 10
-2x = 10 - 4
-2x = 6 / : (-2)
x = -3

d) -(2x-1) =4
-2x + 1 = 4
-2x = 4 -1
-2x = 3 /: (-2)
x = -3/2
x = -1 i 1/2

g) -(4+x) = 2(3-x)
-4 - x = 6 - 2x
-x + 2x = 6 + 4
x = 10

h) 3(y+6) -y= 2(y+9)
3y + 18 -y = 2y + 18
2y - 2y = 18 - 18
0 = 0
23 4 23
2010-03-22T22:23:42+01:00
A)
-3x = 2x-10
10=2x+3x
10=5x
2=x

c)
10 =4-2x
10-4=-2x
6=-2x
-3=x

d)
-(2x-1) =4
-2x+1=4
-2x=4-1
-2x=3
x=-1,5

g)
-(4+x) = 2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

h)
3(y+6) -y= 2(y+9)
3y+18-y=2y+18
2y+18=2y+18
2y-2y=18-18
0=0
10 3 10
2010-03-22T22:24:36+01:00
A) -3x= 2x - 10
-3x-2x=-10
-5x=-10 /*(-1)
5x=10
x=2

c) 10 = 4 - 2x
2x=4-10
2x=-6
x=-3

d) -(2x-1) =4
-2x + 1 = 4
-2x = 4 -1
-2x = 3 /: (-2)
x = -3/2
x = -1 i 1/2

g) -(4+x) = 2(3-x)
-4 - x = 6 - 2x
-x + 2x = 6 + 4
x = 10

h) 3(y+6) -y= 2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0

21 2 21